400 MPa ultrahigh-strength magnesium-lithium alloy as well as preparation method and application thereof
Through alloy composition design and deformation heat treatment process, the problems of insufficient tensile strength of magnesium lithium alloy and complex preparation process are solved, and the preparation of 400MPa grade ultra-high strength magnesium lithium alloy is realized, which simplifies the process flow and reduces costs. It is suitable for aerospace and other fields. .
Patent Information
- Application Number
- CN202411359928.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
AI Technical Summary
The tensile strength of magnesium lithium alloys is insufficient and the preparation process is complex, resulting in limited applications in aerospace and weapons and equipment.
Through the alloy composition design, a variety of heat-stable rare earth second phase and Zr elements are introduced, and a deformation heat treatment process combined with solid solution heat treatment, hot extrusion and rolling are adopted to optimize the ratio of Zn and rare earth elements to realize magnesium lithium alloy High intensity improvement.
It significantly improves the tensile strength of magnesium lithium alloy to 400MPa, simplifies the process flow, reduces production costs, realizes the feasibility of industrial production, and improves the plasticity of the alloy on the basis of ensuring strength.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of plastic processing of magnesium-lithium alloys, and in particular relates to a performance improvement and optimized preparation process of an ultra-high-strength magnesium-lithium alloy, and specifically relates to a 400MPa ultra-high-strength magnesium-lithium alloy and a preparation method and application thereof. The present invention introduces more thermally stable rare earth second phases through the design of alloy components, and significantly improves the strength of the magnesium-lithium alloy through a deformation heat treatment process combining solid solution, extrusion and rolling, and can realize industrial production. Background Art
[0002] Magnesium-lithium alloy is considered to be the lightest structural metal material in the world. It has low density, high elastic modulus, high specific stiffness and specific strength, good electrical conductivity and thermal conductivity, and combines the ultra-light, high-strength and high-plasticity characteristics of aluminum alloy, magnesium-aluminum alloy and carbon fiber composite materials. Therefore, in the context of energy conservation and emission reduction and the pursuit of lightweight, magnesium-lithium alloy has broad application prospects in aerospace, weapons, electronics and other fields, and is known as the green engineering material of the 21st century. However, the tensile strength of commercial Mg-Li alloy generally does not exceed 250MPa. With the demand for lightweight technology in aerospace and weapon equipment, magnesium-lithium alloy is limited to a wider range of applications due to its low strength.
[0003] Al and Zn elements have the largest solid solubility in Mg-Li alloys, which can produce significant solid solution strengthening effects, but the plasticity of the alloy after solid solution treatment is poor, and there is aging softening behavior. Although the solid solution strengthening contribution of Zn element per unit mass is not as good as that of Al element, different rare earth second phases can be introduced into Mg-Zn-Y and Mg-Zn-Y-Zr alloy systems according to the Zn / Y ratio, such as the Chinese patent with publication number CN1948532A (a quasi-crystalline phase strengthened magnesium-lithium alloy and its preparation method) and the Chinese patent with publication number CN107541630A (effective use of rare earth element Y to strengthen dual-phase Mg-Li-Zn-Y magnesium-lithium alloy and its preparation method), which mainly introduces I phase (Mg3Zn6Y) and uses a deformation heat treatment process to refine I phase, thereby obtaining a high-strength magnesium-lithium alloy with excellent plasticity and a tensile strength of up to 350MPa. In the "Preparation and Study of Microstructure and Mechanical Properties of Mg-Li-Zn-Y-Zr Alloy Thin Plates [D], Xi'an University of Technology", Xu Xinfeng et al. prepared Mg-7.5Li-3.5Zn-xY-0.5Zr (x = 1, 2, 3wt.%) thin plates with a tensile strength of 264MPa by reciprocating extrusion, forward extrusion, and cold rolling. However, the magnesium-lithium alloys described in the above patents and literature have a single type of second phase, and the process operation is complicated and the reproducibility is low. In "Fabrication of Nanocrystalline High-Strength MagnesiumLithium Alloy by Rotary Swaging [J], Adv. Eng. Mater. 2021, 2100666", Chen et al. used a rotary forging process to introduce high-density twins and nano-stack faults into Mg-4Li-3Al-3Zn (wt.%), so that the alloy obtained a room temperature tensile strength of 511MPa magnesium-lithium alloy, which is the highest strength reported in the magnesium-lithium alloy system.
[0004] However, products processed by rotary forging face the problem of uneven structure between the core and the edge, which leads to different performance between the core and the edge. At the same time, rotary forging is only suitable for the preparation of fasteners and its application is limited. In addition, Mg-Li-Al-Zn alloys face aging softening and unstable mechanical properties.
[0005] In view of the low strength of magnesium-lithium alloy and the complicated preparation process of the currently disclosed high-strength magnesium-lithium alloy, the present invention provides an ultra-high-strength magnesium-lithium alloy preparation process that is easy to operate and can quickly achieve large-scale plate production. The present invention introduces I phase, W phase, Mg phase, and W phase by designing the alloy composition and combining the deformation heat treatment process. 24There are multiple strengthening phases and thermally stable phases such as Y5 phase, MgZn phase, Mg3Bi2 phase, etc. Adding a small amount of Zr element can further refine the grains, and by exploring the better deformation process, a large number of dislocations and twins are introduced inside the finer grains, achieving the synergistic improvement of second phase strengthening and deformation strengthening, breaking through the limit of 400MPa ultra-high strength magnesium-lithium alloy. Summary of the invention
[0006] The purpose of the present invention is to provide a 400MPa ultra-high strength magnesium-lithium alloy and a preparation method thereof, so as to ensure that the magnesium-lithium alloy has a low density and can be mass-produced while improving the strength of the alloy.
[0007] The present invention mainly utilizes the solid solution strengthening effect of Zn element and the optimized ratio between Zn element and rare earth element, and obtains a high-strength magnesium-lithium alloy by improving the deformation heat treatment process, so that the tensile strength of the magnesium-lithium alloy reaches 400MPa, and the production of batch plates can be quickly realized while ensuring the strength. The process adopted by the present invention is simple and easy to operate, the production cost is low and controllable, and it has practical industrial application prospects.
[0008] The present invention further proposes the application of the 400MPa ultra-high strength magnesium-lithium alloy.
[0009] Based on the above purpose, the present invention adopts the following technical solutions:
[0010] A 400MPa ultra-high strength magnesium-lithium alloy is composed of the following components in mass percentage: Li: 4.0-8.0%; Zn: 4.5-7.5%; RE: 1.3-4.0%; Zr: 0.2-1.0%; Bi: 0.1-0.5%; the balance is Mg (the impurity content needs to be strictly controlled, and the inevitable impurity content is ≤0.01wt.%).
[0011] Furthermore, the 400MPa ultra-high strength magnesium-lithium alloy is composed of the following components in mass percentage: Li: 5.5-8.0%; Zn: 5.5-6.5%; RE: 1.5-3.0%; Zr: 0.2-1.0%; Bi: 0.1-0.5%; the remainder is Mg (the impurity content must be strictly controlled, and the unavoidable impurity content is ≤0.01wt.%).
[0012] Specifically, RE is one or more of the rare earth elements Y, Gd, Nd, Er, La, and Dy.
[0013] Specifically, the mass ratio of Zn / RE is (1.1-4.3):1.
[0014] Further, based on a general inventive concept, the present invention also provides a method for preparing the 400MPa ultra-high strength magnesium-lithium alloy, comprising the following steps:
[0015] S1 vacuum melting and casting: the ingredients are prepared according to the ratio of the magnesium-lithium alloy elements, loaded into a crucible in sequence, and placed in a vacuum induction furnace, and argon gas is introduced to perform vacuum melting and casting to obtain a high-purity magnesium-lithium alloy ingot;
[0016] S2 Solution heat treatment: The high purity magnesium-lithium alloy ingot of step S1 is subjected to solution heat treatment, then air-cooled to room temperature, and then machined to remove the surface oxide layer and defects to obtain a prefabricated extrusion billet;
[0017] S3 hot extrusion: the extruded billet obtained in step S2 is reheated, deformed by hot extrusion, and then water-cooled to room temperature to obtain a sheet;
[0018] S4 rolling: the plate after hot extrusion in step S3 is rolled by a composite deformation process of hot rolling + cold rolling to achieve cumulative deformation, and air-cooled to room temperature after rolling to obtain the final product.
[0019] Specifically, in step S1, the raw materials used in the batching are pure magnesium, pure lithium, pure aluminum, pure zinc and intermediate alloys Mg-30Y, Mg-10Bi and Mg-30Zr.
[0020] Specifically, in step S1, the vacuum melting and casting process is: evacuating to below 10Pa, heating to melt, mechanically stirring 2 to 3 times after melting, and then standing and keeping warm at 700 to 730°C for 10 to 30 minutes for melting, and then casting.
[0021] Specifically, in step S2, the solution heat treatment process is: subjecting the high-purity magnesium-lithium alloy ingot of step S1 to solution heat treatment at a temperature of 400-500° C. for 8 h to 12 h under argon protection.
[0022] Specifically, in step S3, the preheating is: heating the extruded billet obtained in step S2 to 200-350° C. and keeping the temperature for 2-8 hours.
[0023] Furthermore, in step S3, the preheating temperature is preferably 230-350°C.
[0024] Specifically, in step S3, the hot extrusion process parameters are: extrusion billet temperature is 200-350°C, extrusion barrel temperature is 200-350°C, extrusion ratio is not less than 15:1, and extrusion speed is 1-1.5 m / min.
[0025] Furthermore, in step S3, the temperature of the extruded billet is preferably 230-350°C, and the temperature of the extrusion barrel is preferably 220-350°C.
[0026] Specifically, in step S4, the rolling process is hot rolling followed by cold rolling, preferably: the plate after hot extrusion in step S3 is hot rolled at 250-350°C; and then cold rolled at room temperature.
[0027] Specifically, in step S4, during hot rolling, the reduction in each pass does not exceed 15%, and intermediate annealing at 250-350° C. for 5-10 min is performed between each pass, and the total reduction (deformation) in hot rolling is 50%.
[0028] More preferably, in step S4, during hot rolling, the reduction amount per pass is 5% to 15%.
[0029] Specifically, in step S4, during cold rolling, the reduction amount per pass does not exceed 10%.
[0030] More preferably, in step S4, during cold rolling, the reduction amount per pass is 5% to 10%.
[0031] Specifically, in step S4, hot rolling + cold rolling are performed for a total of 18 times.
[0032] Specifically, in step S4, during the entire rolling process, the cumulative total deformation is 75%.
[0033] Specifically, in step S4, during the entire rolling process, the roller speed is 8-15 r / min.
[0034] Specifically, in the method for preparing the 400 MPa ultra-high strength magnesium-lithium alloy, room temperature refers to 25±5°C.
[0035] Furthermore, based on a general inventive concept, the present invention also provides a method for preparing a 400MPa ultra-high strength magnesium-lithium alloy by a solid solution + extrusion + rolling composite deformation method; the ultra-high strength magnesium-lithium alloy can meet the strength requirements of smaller cross-sections in structural parts, and can be used in aerospace, weapon equipment and other fields, and can be used as shells, structural supports, skins, cover plates, etc.
[0036] Furthermore, based on a general inventive concept, the present invention also provides the use of the 400MPa ultra-high strength magnesium-lithium alloy in the preparation of space probes, short-range high-speed aviation vehicles or automotive parts.
[0037] Specifically, the components are shells, structural support components, structural fasteners, skins, cover plates, etc.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. The ultra-high strength magnesium-lithium alloy of the present invention adds the main elements Zn and Y, a small amount of Zr and other RE elements to the binary magnesium-lithium alloy, which can give full play to their respective advantages. The solid solubility of Zn element is relatively large, and it can exert its maximum solid solution strengthening effect. The addition of Y element can effectively introduce I phase, W phase and Mg phase by adjusting the ratio between Zn element and Y element. 24 The Y5 phase has more rare earth second phase. More second phases can play a greater role in strengthening the second phase, and the rare earth second phase is relatively stable, which can effectively resist or slow down the instability of the performance of magnesium-lithium alloys. The introduction of Zr elements can make the grains of the alloy finer. At the same time, the introduction of Bi can produce solid solution strengthening and precipitation strengthening effects, and Mg3Bi2 can strengthen the grain boundaries, which is beneficial to improving heat resistance. The combined effect can achieve a synergistic improvement in strength and plasticity.
[0040] 2. Based on the design of the present invention, the structure of the alloy can be improved by the solution heat treatment process. After the alloy is subjected to high-temperature solution treatment, the coarse non-equilibrium phase in the cast solidification process is dissolved to obtain a supersaturated solid solution. The alloy after the solution heat treatment is subjected to extrusion, hot rolling + cold rolling composite deformation, so that the magnesium-lithium alloy undergoes recrystallization and refinement, disperses and precipitates a large number of nanophases, accumulates a high strain hardening effect, and introduces a large number of nanotwins and high-density dislocations, thereby achieving a synergistic improvement in the strength and plasticity of the magnesium-lithium alloy, and the tensile strength is increased to 400.5MPa at the highest.
[0041] 3. The method for preparing the ultra-high strength magnesium-lithium alloy of the present invention has the characteristics of simple plastic processing procedures, short process, low cost and strong operability. Plastic deformation only involves extrusion and rolling, which can quickly realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The metallographic structure diagram of the ultra-high strength magnesium-lithium alloy before and after solution heat treatment according to Example 1 of the present invention (the left diagram is before treatment, and the right diagram is after treatment);
[0043] Figure 2 The metallographic structure diagrams of the ultra-high strength magnesium-lithium alloy after extrusion and after rolling according to Example 1 of the present invention (the left diagram is after extrusion, and the right diagram is after rolling);
[0044] Figure 3 The room temperature stress-strain curves of Example 1 of the present invention and the comparative cast and extruded states are shown. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0046] Unless otherwise specified, the experimental methods involved in the following examples are all conventional methods; the instruments and equipment used in the following examples are all commercially available conventional instruments and equipment unless otherwise specified; the reagents, raw materials, etc. used in the following examples are all conventional commercially available products and can be obtained from commercial channels unless otherwise specified.
[0047] The room temperature described in the following examples refers to 25±5°C.
[0048] Example 1
[0049] A 400MPa ultra-high strength magnesium-lithium alloy is composed of the following components in mass percentage: 5.5% Li, 6.5% Zn, 2.5% Y, 0.6% Zr, 0.2% Bi, the Zn / Y mass ratio is about 2.5:1, the balance is Mg, and the inevitable impurity content is ≤0.01wt.%.
[0050] The preparation method of the 400MPa ultra-high strength magnesium-lithium alloy includes vacuum melting, solutionizing, hot extrusion, hot rolling, cold rolling and other processes, wherein the Mg element, Li element, Zn element, Y element, Zr element and Bi element are added in the form of pure magnesium, pure lithium, pure aluminum, pure zinc and intermediate alloys Mg-30Y, Mg-10Bi and Mg-30Zr, respectively, wherein the purity of the pure element is ≥99.95%, and the specific steps are as follows:
[0051] S1 Vacuum melting and casting: the required industrial pure magnesium, pure lithium, pure aluminum, pure zinc and intermediate alloys Mg-30Y, Mg-10Bi and Mg-30Zr are prepared according to the above-mentioned magnesium-lithium alloy element ratio, and then they are sequentially loaded into a crucible and placed in a vacuum induction furnace, argon gas is introduced, and the vacuum is evacuated to 10Pa and then heated to melt. After melting, mechanical stirring is performed twice, and then the mixture is placed at 710°C for 25 minutes for smelting, and then cast. During the process, absolute vacuum is ensured to obtain a high-purity magnesium-lithium alloy ingot;
[0052] S2 solution heat treatment: the high purity magnesium-lithium alloy ingot of step S1 is kept at 440°C for 10 hours in an argon atmosphere furnace, air-cooled to room temperature, and then machined to remove the surface oxide layer and defects to obtain a prefabricated extrusion billet;
[0053] S3 hot extrusion: the extrusion blank obtained in step S2 is heated to 350°C and kept for 4 hours for re-preheating, and then hot extrusion deformation is performed. The specific process parameters are: the extrusion blank temperature is 350°C, the extrusion barrel temperature is 350°C, and the extrusion die temperature is 330°C. In this embodiment, the extrusion barrel temperature is kept consistent with the extrusion blank temperature to make the feed temperature more uniform; the extrusion ratio is 16:1; the extrusion speed is 1-1.5 m / min; and then water-cooled to room temperature to obtain a plate;
[0054] S4 hot rolling + cold rolling: the plate after hot extrusion in step S3 is first hot rolled at 300°C, the rolling rollers are at room temperature, the rolling roller speed is 8r / min, the pressing amount per pass is 10%, and each pass needs to be annealed at 350°C for 5 minutes, and the total hot rolling deformation is 50%; then cold rolling is performed, the cold rolling is performed at room temperature, the pressing amount per pass is 5%, and the hot rolling + cold rolling is performed for a total of 18 passes. The total deformation of the magnesium-lithium alloy plate after hot rolling + cold rolling is 75%. After rolling, the plate is air-cooled to room temperature to obtain the final product.
[0055] Figure 1 The metallographic structure diagram of the ultra-high strength magnesium-lithium alloy before and after solution heat treatment described in Example 1 (the left picture is before treatment, and the right picture is after treatment); Figure 2 The metallographic structure diagrams of the ultra-high strength magnesium-lithium alloy after extrusion and after rolling described in Example 1 (the left diagram is after extrusion, and the right diagram is after rolling); Figure 3 The room temperature stress-strain curves of Example 1 and the comparative cast and extruded states are shown in FIG. Figure 1 , Figure 2 , Figure 3 It can be found that the alloy performance is slightly improved after extrusion deformation. Through further rolling deformation, the tensile strength of the alloy is increased from about 270MPa in the extruded state to about 400MPa, an increase of about 48%. Compared with the tensile performance of the cast state, the improvement is about 88%. Therefore, the strength of magnesium-lithium alloy can be greatly improved through the alloying composition design and the deformation heat treatment process combining solid solution + extrusion + hot rolling / cold rolling.
[0056] The tensile test was carried out in accordance with GB / T 16865 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products. The tensile strength R m =400.5MPa, yield strength R 0.2 =358.2MPa, elongation A=9.4%.
[0057] Example 2
[0058] A 400MPa ultra-high strength magnesium-lithium alloy is composed of the following components in mass percentage: 6% Li, 6% Zn, 2% Y, 0.5% Zr, 0.2% Bi, the Zn / Y mass ratio is about 3:1, the balance is Mg, and the inevitable impurity content is ≤0.01wt.%.
[0059] The preparation method of the 400MPa ultra-high strength magnesium-lithium alloy includes vacuum melting, solutionizing, hot extrusion, hot rolling, cold rolling and other processes, wherein the Mg element, Li element, Zn element, Y element, Zr element and Bi element are added in the form of pure magnesium, pure lithium, pure aluminum, pure zinc and intermediate alloys Mg-30Y, Mg-10Bi and Mg-30Zr, respectively, wherein the purity of the pure element is ≥99.95%, and the specific steps are as follows:
[0060] S1 Vacuum melting and casting: the required industrial pure magnesium, pure lithium, pure aluminum, pure zinc and intermediate alloys Mg-30Y, Mg-10Bi and Mg-30Zr are prepared according to the above-mentioned magnesium-lithium alloy element ratio, and then they are sequentially loaded into a crucible and placed in a vacuum induction furnace, argon gas is introduced, and the vacuum is evacuated to 10Pa and then heated to melt. After melting, mechanical stirring is performed twice, and then the mixture is placed at 710°C for 25 minutes for smelting, and then cast. During the process, absolute vacuum is ensured to obtain a high-purity magnesium-lithium alloy ingot;
[0061] S2 solution heat treatment: the high purity magnesium-lithium alloy ingot of step S1 is kept at 440°C for 10 hours in an argon atmosphere furnace, air-cooled to room temperature, and then machined to remove the surface oxide layer and defects to obtain a prefabricated extrusion billet;
[0062] S3 hot extrusion: the extruded billet obtained in step S2 is heated to 330°C and kept for 4 hours for re-preheating, and then hot extrusion deformation is performed. The specific process parameters are: extrusion billet temperature is 330°C, extrusion barrel temperature is 280°C, extrusion die temperature is 260°C, extrusion ratio is 16:1, extrusion speed is 1-1.5m / min, and then water-cooled to room temperature to obtain a sheet;
[0063] S4 hot rolling + cold rolling: the plate after hot extrusion in step S3 is first hot rolled at 330°C, the rollers are at room temperature, the roller speed is 8r / min, the pressing amount of each pass is 10%, and each pass needs to be annealed at 350°C for 5 minutes, and the total hot rolling deformation is 50%; then cold rolling is performed, the cold rolling is performed at room temperature, the pressing amount of the first two passes is 10%, the pressing amount of the middle multiple passes and the last pass is 5%, and the hot rolling + cold rolling is performed for a total of 18 passes, and the total deformation of the magnesium-lithium alloy plate after hot rolling + cold rolling is 75%. After rolling, it is air-cooled to room temperature to obtain the final product.
[0064] The tensile test was carried out in accordance with GB / T 16865 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products. The tensile strength R m =372.2MPa, yield strength R 0.2 =330.3MPa, elongation A=15.7%.
[0065] Example 3
[0066] A 400MPa ultra-high strength magnesium-lithium alloy is composed of the following components in mass percentage: 7% Li, 6% Zn, 2.5% Y, 0.5% Zr, 0.2% Bi, the Zn / Y mass ratio is about 2.5:1, the balance is Mg, and the inevitable impurity content is ≤0.01wt.%.
[0067] The preparation method of the 400MPa ultra-high strength magnesium-lithium alloy includes vacuum melting, solutionizing, hot extrusion, hot rolling, cold rolling and other processes, wherein the Mg element, Li element, Zn element, Y element, Zr element and Bi element are added in the form of pure magnesium, pure lithium, pure aluminum, pure zinc and intermediate alloys Mg-30Y, Mg-10Bi and Mg-30Zr, respectively, wherein the purity of the pure element is ≥99.95%, and the specific steps are as follows:
[0068] S1 Vacuum melting and casting: the required industrial pure magnesium, pure lithium, pure aluminum, pure zinc and intermediate alloys Mg-30Y, Mg-10Bi and Mg-30Zr are prepared according to the above-mentioned magnesium-lithium alloy element ratio, and then they are sequentially loaded into a crucible and placed in a vacuum induction furnace, argon gas is introduced, and the vacuum is evacuated to 10Pa and then heated to melt. After melting, mechanical stirring is performed twice, and then the mixture is placed at 710°C for 25 minutes for smelting, and then cast. During the process, absolute vacuum is ensured to obtain a high-purity magnesium-lithium alloy ingot;
[0069] S2 solution heat treatment: the high purity magnesium-lithium alloy ingot of step S1 is kept at 400°C for 10 hours in an argon atmosphere furnace, air-cooled to room temperature, and then machined to remove the surface oxide layer and defects to obtain a prefabricated extrusion billet;
[0070] S3 hot extrusion: the extruded billet obtained in step S2 is heated to 250°C and kept for 4 hours for re-preheating, and then hot extrusion deformation is performed. The specific process parameters are: extrusion billet temperature is 250°C, extrusion barrel temperature is 250°C, extrusion die temperature is 230°C, extrusion ratio is 16:1, extrusion speed is 1-1.5m / min, and then water-cooled to room temperature to obtain a sheet;
[0071] S4 hot rolling + cold rolling: the plate after hot extrusion in step S3 is first hot rolled at 300°C, the rolling rollers are at room temperature, the rolling roller speed is 8r / min, the pressing amount per pass is 10%, and each pass needs to be annealed at 300°C for 5 minutes, and the total hot rolling deformation is 50%; then cold rolling is performed, the cold rolling is performed at room temperature, the pressing amount per pass is 5%, and the hot rolling + cold rolling is performed for a total of 18 passes. The total cumulative deformation of the magnesium-lithium alloy plate by hot rolling + cold rolling is 75%, and the final product is obtained by air cooling to room temperature after rolling.
[0072] The tensile test was carried out in accordance with GB / T 16865 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products. The tensile strength R m =348.9MPa, yield strength R 0.2 =313.6MPa, elongation A=19.5%.
[0073] Example 4
[0074] A 400MPa ultra-high strength magnesium-lithium alloy is composed of the following components in mass percentage: 8% Li, 6% Zn, 4% Y, 0.5% Zr, 0.3% Bi, the Zn / Y mass ratio is about 1.5:1, the balance is Mg, and the inevitable impurity content is ≤0.01wt.%.
[0075] The preparation method of the 400MPa ultra-high strength magnesium-lithium alloy includes vacuum melting, solutionizing, hot extrusion, hot rolling, cold rolling and other processes, wherein the Mg element, Li element, Zn element, Y element, Zr element and Bi element are added in the form of pure magnesium, pure lithium, pure aluminum, pure zinc and intermediate alloys Mg-30Y, Mg-10Bi and Mg-30Zr, respectively, wherein the purity of the pure element is ≥99.95%, and the specific steps are as follows:
[0076] S1 Vacuum melting and casting: the required industrial pure magnesium, pure lithium, pure aluminum, pure zinc and intermediate alloys Mg-30Y, Mg-10Bi and Mg-30Zr are prepared according to the above-mentioned magnesium-lithium alloy element ratio, and then they are sequentially loaded into a crucible and placed in a vacuum induction furnace, argon gas is introduced, and the vacuum is evacuated to 10Pa and then heated to melt. After melting, mechanical stirring is performed twice, and then the mixture is placed at 710°C for 25 minutes for smelting, and then cast. During the process, absolute vacuum is ensured to obtain a high-purity magnesium-lithium alloy ingot;
[0077] S2 Solution heat treatment: The high purity magnesium-lithium alloy ingot of step S1 is kept at 460°C for 10 hours in an argon atmosphere furnace, air-cooled to room temperature, and then machined to remove the surface oxide layer and defects to obtain a prefabricated extrusion billet;
[0078] S3 hot extrusion: the extruded billet obtained in step S2 is heated to 250°C and kept for 4 hours for re-preheating, and then hot extrusion deformation is performed. The specific process parameters are: extrusion billet temperature is 250°C, extrusion barrel temperature is 250°C, extrusion die temperature is 230°C, extrusion ratio is 16:1, extrusion speed is 1-1.5m / min, and then water-cooled to room temperature to obtain a sheet;
[0079] S4 hot rolling + cold rolling: the plate after hot extrusion in step S3 is first hot rolled at 300°C, the rolling rollers are at room temperature, the rolling roller speed is 8r / min, the pressing amount per pass is 10%, and each pass needs to be annealed at 280°C for 5 minutes, and the total hot rolling deformation is 50%; then cold rolling is performed, the cold rolling is performed at room temperature, the pressing amount per pass is 5%, and the hot rolling + cold rolling is performed for a total of 18 passes. The total cumulative deformation of the magnesium-lithium alloy plate by hot rolling + cold rolling is 75%, and the final product is obtained by air cooling to room temperature after rolling.
[0080] The tensile test was carried out in accordance with GB / T 16865 Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products. The tensile strength R m =387.4MPa, yield strength R 0.2 =314.2MPa, elongation A=23.8%.
[0081] The mechanical property test results of the ultra-high strength magnesium-lithium alloys prepared in Examples 1, 2, 3, and 4 are shown in Table 1.
[0082] Table 1 Mechanical properties test of ultra-high strength magnesium-lithium alloys prepared in different embodiments
[0083]
[0084] It can be concluded from Examples 1-4 and Table 1 that the strength of the alloy gradually decreases with the increase of Li content, but the elongation continues to increase. Among them, through alloying design, when the Li content is designed to be 5.5%, the Zn / Y mass ratio is about 2.5, and the balance is Mg, the alloy has a high strength performance of 400.5MPa in tensile strength, 358.2MPa in yield strength, and 9.4% in elongation after fracture after deformation heat treatment, as shown in Example 1. In addition, when the Li content is designed to be 8%, the Zn / Y mass ratio is about 1.5, and the balance is Mg, a better performance of both strong and plastic properties is obtained, as shown in Example 4.
[0085] The above describes the specific implementation examples of the present invention. It should be understood that the present invention is not limited to the above specific implementation examples. Those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A 400MPa ultra-high strength magnesium-lithium alloy, characterized in that: It is composed of the following components in mass percentage: Li: 4.0-8.0%; Zn: 4.5-7.5%; RE: 1.3-4.0%; Zr: 0.2-1.0%; Bi: 0.1-0.5%; and the balance is Mg.
2. The 400MPa ultra-high strength magnesium-lithium alloy according to claim 1, characterized in that: RE is one or more of the rare earth elements Y, Gd, Nd, Er, La, and Dy; the mass ratio of Zn / RE is (1.1~4.3):
1.
3. The method for preparing the 400MPa ultra-high strength magnesium-lithium alloy according to claim 1 or 2, characterized in that: The steps include: S1 vacuum melting and casting: preparing the magnesium-lithium alloy according to the ratio of elements, placing the alloy in a vacuum induction furnace, introducing argon gas, and performing vacuum melting and casting to obtain a high-purity magnesium-lithium alloy ingot; S2 Solution heat treatment: Solution heat treatment of the high purity magnesium-lithium alloy ingot in step S1, followed by air cooling to room temperature, and then removing the surface oxide layer and defects to obtain a prefabricated extrusion billet; S3 hot extrusion: the extruded billet obtained in step S2 is reheated, deformed by hot extrusion, and then water-cooled to room temperature to obtain a sheet; S4 rolling: the plate after hot extrusion in step S3 is rolled by a composite deformation process of hot rolling + cold rolling to achieve cumulative deformation, and air-cooled to room temperature after rolling to obtain the final product.
4. The preparation method according to claim 3, characterized in that: The vacuum melting and casting process is as follows: evacuate to below 10Pa, heat to melt, mechanically stir 2 to 3 times after melting, then stand at 700 to 730°C for 10 to 30 minutes for melting, and then cast.
5. The preparation method according to claim 3, characterized in that: In step S2, the solution heat treatment process is: subjecting the high purity magnesium-lithium alloy ingot of step S1 to solution heat treatment at a temperature of 400-500° C. for 8 h to 12 h under argon protection.
6. The preparation method according to claim 3, characterized in that: In step S3, the preheating is: heating the extruded billet obtained in step S2 to 200-350° C. and keeping the temperature for 2-8 hours.
7. The preparation method according to claim 3, characterized in that: In step S3, the hot extrusion process parameters are: extrusion billet temperature is 200-350°C, extrusion barrel temperature is 200-350°C, extrusion ratio is not less than 15:1, and extrusion speed is 1-1.5 m / min.
8. The preparation method according to claim 3, characterized in that: In step S4, the rolling process is hot rolling followed by cold rolling, specifically: the plate after hot extrusion in step S3 is hot rolled at 250-350°C to deform by 50%; then cold rolled at room temperature, and the total deformation of hot rolling + cold rolling is 75%.
9. The preparation method according to claim 3, characterized in that: In step S4, during hot rolling, the reduction in each pass does not exceed 15%, and intermediate annealing at 250-350°C for 5-10 minutes is performed between each pass; In step S4, during cold rolling, the reduction in each pass does not exceed 10%.
10. Use of the 400 MPa ultra-high strength magnesium-lithium alloy according to claim 1 or 2 in the preparation of space probes, short-range high-speed aircraft or automotive parts.
Citation Information
Cited By
Preparation method of layered composite sheet containing quasicrystal phase
CN120515812A